Caesarean Delivery- a Pressured Choice for Women: A Meta-Analysis of 23 Cross-Sectional Studies - Ananna, Munira Nargis; Hossain, Md Belal (Dhaka University Journal of Science, 2023)
The aim of this study is to investigate the associated factors which influence women to choose caesarean delivery or C-Section (CS) and to quantify the contribution of these factors. This meta-analysis indicates that for maternal age at birth, age group 20-29 years is 1.45 times more likely to choose CS as compared to the age group ≤19 years [OR= 1.45; Overall effect Z=4.57, p<0.01], for mother’s education level educated mothers are 8.86 times more likely to choose CS as compared to the uneducated mothers[OR= 8.86; Z=4.10, p<0.01].For marital status OR=1.40;Z= 1.34, p=0.18, for residence OR= 1.02;Z=0.11, p= 0.91, for mother’s employment status OR= 0.97;Z=-0.12, p= 0.90 and for receiving Antenatal Care between 1-3 times versus 0 time OR= 2.11;Z=1.84, p= 0.07. Mother’s economic status [OR= 1.41;Z=3.43, p<0.01], whether previous CS [OR=9.39; Z=2.24,p=0.03] and type of delivery facility [OR= 0.67; Z=-2.03, p= 0.04] are found to be significant factors for choosing CS over normal delivery. Dhaka Univ. J. Sci. 71(1): 1-5, 2023 (Jan)